2022
DOI: 10.1002/edm2.338
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes on COVID‐19 mortality and hospital outcomes from a global perspective: An umbrella systematic review and meta‐analysis

Abstract: Introduction To date, COVID‐19 has claimed 4.9 million lives. Diabetes has been identified as an independent risk factor of serious outcomes in people with COVID‐19 infection. Whether that holds true across world regions uniformly has not been previously assessed. Methods This study offers the first umbrella systematic review and meta‐analysis to analyse the collective and geographically stratified mortality, ICU admission, ventilation requirement, illness severity and discharge rate amongst patients with diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 188 publications
(270 reference statements)
6
35
2
3
Order By: Relevance
“…Third, given the significant variations in disease severity and mortality with geographical locations and different phases of the pandemic [ 5 ], the inclusion of predominantly Turkish studies may not justify the extrapolation of our results to other countries and ethnic groups. Fourth, although comorbidities have been found to contribute to mortality and severity in patients diagnosed with COVID-19 [ 56 , 57 ], the lack of relevant information precluded a subgroup analysis of their potential impacts on our study outcomes. Fifth, of the 10 included studies, only four provided relevant information about the equipment and procedures for fibrinogen measurement [ 24 , 33 , 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, given the significant variations in disease severity and mortality with geographical locations and different phases of the pandemic [ 5 ], the inclusion of predominantly Turkish studies may not justify the extrapolation of our results to other countries and ethnic groups. Fourth, although comorbidities have been found to contribute to mortality and severity in patients diagnosed with COVID-19 [ 56 , 57 ], the lack of relevant information precluded a subgroup analysis of their potential impacts on our study outcomes. Fifth, of the 10 included studies, only four provided relevant information about the equipment and procedures for fibrinogen measurement [ 24 , 33 , 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis, including 158 observational studies with a total of 270,212 participants, of whom 57,801 had diabetes, reported that people with diabetes were at higher risk of COVID-19-related mortality with an OR 1.87 (95% CI 1.61–2.17) and higher risk of ICU admission (1.59 [95% CI 1.15–2.18]) and ventilation requirements (1.44 [95% CI 1.20–1.73]) in comparison to subjects without diabetes [ 11 ]. In addition, cardiovascular disease is common comorbidity observed in patients with COVID-19, associated with increased severity and mortality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As well, pre-existing diabetes mellitus has been considered a risk factor for increased COVID-19 severity and worse outcomes, including higher mortality, irrespective of age and comorbidity status [ 7 ]. The estimates of diabetes prevalence in those who have died of COVID-19 range from 20 to 30% [ 10 , 11 ]. A recent meta-analysis showed that people with diabetes were at higher risk of COVID-19-related mortality in comparison to people without diabetes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 outbreak has recently changed the daily routine of children and adolescents, with a tendency for a sedentary lifestyle and altered dietary habits. Adult patients with T1DM have been included in the high-risk group for COVID-19 infection with high mortality and morbidity rate and priority was given once vaccination was available ( 54 ). As regards children with T1DM, in the first year of pandemics evidence was weak.…”
Section: Narrative Reviewmentioning
confidence: 99%